Structure–Activity Relationships on Cinnamoyl Derivatives as Inhibitors of p300 Histone Acetyltransferase. (12th April 2017) - Madia, Valentina Noemi; Benedetti, Rosaria; Barreca, Maria Letizia; Ngo, Liza; Pescatori, Luca; Messore, Antonella; Pupo, Giovanni; Saccoliti, Francesco; Valente, Sergio; Mai, Antonello; Scipione, Luigi; Zheng, Yujun George; et al.
Abstract: Human p300 is a polyhedric transcriptional coactivator that plays a crucial role in acetylating histones on specific lysine residues. A great deal of evidence shows that p300 is involved in several diseases, including leukemia, tumors, and viral infection. Its involvement in pleiotropic biological roles and connections to diseases provide the rationale to determine how its modulation could represent an amenable drug target. Several p300 inhibitors (i.e., histone acetyltransferase inhibitors, HATis) have been described so far, but they all suffer from low potency, lack of specificity, or low cell permeability, which thus highlights the need to find more effective inhibitors. Our cinnamoyl derivative, 2, 6‐bis(3‐bromo‐4‐hydroxybenzylidene)cyclohexanone (RC56), was identified as an active and selective p300 inhibitor and was proven to be a good hit candidate to investigate the structure–activity relationship toward p300. Herein, we describe the design, synthesis, and biological evaluation of new HATis structurally related to our hit; moreover, we investigate the interactions between p300 and the best‐emerged hits by means of induced‐fit docking and molecular‐dynamics simulations, which provided insight into the peculiar chemical features that influence their activity toward the targeted enzyme. Abstract : HAT trick : Histone acetyltransferase (HAT) is an attractive anticancer target. Several HAT inhibitors have been identified, but they all exhibit low potency or pharmacodynamics limits. Herein we report the design and synthesis along with biological evaluations and theoretical investigations of potent and selective cinnamoyl compounds, highlighting the peculiar features required to develop an effective HAT inhibitor.